VISION AND STRATEGY REGARDING THE PARKING LOTS WITH ELEVATORS - Carmen Elisabeta RADU; Edward RĂSCHITOR; Viorel POPESCU; Iosif TEMPEA (Fiabilitate şi Durabilitate)
Parking services play an important part in the urban mobility, accessibility and economic development. The design and accomplishment of the intelligent parking lot equipped with elevators and wireless systems is also efficient and profitable. The mechanism is equipped with elevator.